'I'm the boss of the Stiemerbeek valley!' Reconsidering children's empowerment in participatory design from the perspective of infrastructuring. Issue 3 (3rd July 2022) - Schepers, Selina; Schoffelen, Jessica; Zaman, Bieke; Dreessen, Katrien
ABSTRACT: Although researchers and designers have paid attention to children's empowerment in Participatory Design (PD) processes, there is a lacuna in research into manifestations of empowerment in and as a result of PD processes concerned with the building of dynamic infrastructures. In a response, we conducted a case study in which 10–12-year-olds participated in designing prototypes related to a local nature area and reconsidered existing views on empowerment. The findings resulted in (1) a broad operationalisation of the critical form of empowerment; (2) a mapping of the possibilities for empowerment in informal time frames next to traditional, project-related time frames; and (3) an extended analytical framework for the span of activities considered to be empowering in PD processes. The contribution of this study is a comprehensive understanding and lingua franca to consider children's empowerment in relation to infrastructuring. This infrastructural view on empowerment allows to include notions of active citizenship and empowerment-in-use in the discourse and analysis on children's empowerment, placing design participation in a holistic context, beyond the formal participation in the design process.